Interface formation between calcium and electron-irradiated poly(3-hexylthiophene) - Bebensee, Fabian; Zhu, Junfa; Baricuatro, J. H.; Farmer, Jason A.; Bai, Yun; Steinrück, Hans-Peter; Campbell, C. T.; Gottfried, Michael (Langmuir, 2010)
The adsorption of Ca on electron-irradiated poly(3-hexylthiophene) (P3HT) surfaces at 300 K (E = 100 eV) has been studied by adsorption microcalorimetry, atomic beam/surface scattering, X-ray photoelectron spectroscopy (XPS), and low-energy He ion scattering spectroscopy (LEIS). The results are compared to previous studies of Ca adsorption on pristine P3HT. The major structural effect of electron irradiation is a substantial increase in the fraction of unsaturated carbon atoms, probably a result of electron-induced hydrogen abstraction from the hexyl chains and formation of new C=C double bonds. No loss of sulfur was observed. The combined XPS, LEIS, and calorimetry data indicate that the reaction and growth behavior of Ca on P3HT surfaces is not significantly affected by this electron damage, apart from an increased sticking probability at low coverages. The sticking probability of Ca on the irradiated P3HT is initially 0.63, compared to 0.36 on the pristine surface. It increases with coverage, approaching unity between 4 and 5 ML. The heat of adsorption stays nearly constant at 405 kJ/mol up to a coverage of 0.6 ML, which is ascribed to Ca diffusing below the surface and forming CaS clusters by abstraction of sulfur from the thiophene rings, based on XPS and LEIS data. The heat of adsorption then decreases gradually until it reaches the heat of sublimation of bulk Ca, 178 kJ/mol, by 4 ML; this is attributed to the formation of 3D Ca islands on top of the polymer, which eventually coalesce into a continuous Ca film by 11 ML. The heat of reaction versus coverage and the ultimate depth up to which the Ca atoms react with the polymer thiophene groups (∼3 nm) are nearly independent of electron damage, except for a difference in the heat of adsorption below 0.1 ML associated with defects or impurities. The increase in initial sticking probability caused by electron damage is attributed to stronger bonding of Ca adatoms to unsaturated versus saturated hydrocarbons. These very weakly held Ca adatoms are transient precursors to the two reactions which dominate the measured heat of adsorption (reaction with thiophene units and Ca cluster formation), but they can also desorb in this three-path kinetic competition. Mass spectrometer data show that these precursors have longer surface residence times on the electron-damaged surface. © 2010 American Chemical Society.